EQUITY IN EDUCATION BUDGET DISTRIBUTION: AN ANALYSIS OF INTER-REGIONAL INEQUALITY FROM A FISCAL EQUATY PERSPECTIVE IN EAST KALIMANTAN - Widyatmike Gede Mulawarman; Nurhadi; Anggrayani; Arwiah; Dyah Retno Sulistyani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Access to quality education is a constitutional right, but geographic and economic disparities often create gaps in education funding. This study aims to analyze the extent to which the distribution of education budgets in districts/cities in East Kalimantan Province meets the principles of fiscal equity. The primary focus is on identifying unequal allocations of education spending and the factors that drive disparities between resource-rich and underdeveloped regions. This study uses a descriptive quantitative approach with secondary data sourced from the most recent Budget Realization Reports (LRA) of districts/cities in East Kalimantan. Fiscal equity analysis is measured using the Gini Index to assess the degree of distribution inequality and the Coefficient of Variation to measure the dispersion of spending per student. Furthermore, horizontal equity analysis is used to compare equality between regions with different fiscal capacities. The analysis shows that significant disparities persist in education budget allocation in East Kalimantan. Regions with high natural resource (SDA) revenue sharing tend to have student education spending far exceeding the provincial average, while satellite and remote regions experience fiscal constraints. Although the 20% spending mandate has been administratively met, the effectiveness of its distribution does not fully reflect the principle of equity based on real regional needs (need-based distribution). This inequality indicates that reliance on regional original revenues and revenue-sharing funds creates a gap in the quality of educational infrastructure and human resources between regions. A fiscal equity perspective calls for intervention mechanisms through more asymmetric financial aid funds to balance weak regional fiscal capacity. Without distribution policy reform, education disparities in East Kalimantan risk widening long-term socio-economic disparities in the buffer zone of the Indonesian Capital City (IKN).